2015
DOI: 10.17645/pag.v3i1.82
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Differences in Scientific Expertise Use: The Politics of Pesticides

Abstract: Despite the growing importance of EU regulatory agencies in European decision-making, academic literature is missing a systematic explanation of how regulatory agencies actually contend with their core tasks of providing scientific advice to EU institutions. The article contributes to the theoretical explanation of when and under what conditions different uses of scientific expertise prevail. In particular, it focuses on theoretical explanations leading to strategic substantiating use of expertise followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…For all the discourse on de-politicisation, their areas of operation are often heavily politicised. The European Food Safety Authority (EFSA) assessments on GMOs and pesticides (most recently glyphosate), for instance, have been the subject of heavy public controversy (Groenleer 2009;Rimkutė 2015Rimkutė , 2018b).…”
Section: Eu Agencies and Reputationmentioning
confidence: 99%
“…For all the discourse on de-politicisation, their areas of operation are often heavily politicised. The European Food Safety Authority (EFSA) assessments on GMOs and pesticides (most recently glyphosate), for instance, have been the subject of heavy public controversy (Groenleer 2009;Rimkutė 2015Rimkutė , 2018b).…”
Section: Eu Agencies and Reputationmentioning
confidence: 99%
“…However, the regulation of risks and hazards is highly polarized. Scholars observe that regulatory agencies' scientific practices—that is, the ways in which scientific knowledge is used in risk assessments—vary considerably (Jasanoff ; Rothstein et al ; Rimkutė , ). The debates between independent regulators become even more heated when it comes to environmental, chemical or foodstuff policy‐making (Lodge and Wegrich ; Lofstedt and Schlag ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasing relevance of regulatory agencies in risk governance, this study proposes an explanation of how risk regulators cope with their key duties of delivering scientific advice to political organizations. Scholars in the field have observed that scientific knowledge and technical expertise can have many functions in regulatory politics (Schrefler ; Rimkutė ). However, endeavours to examine the ways in which scientific knowledge is used in risk assessments, as well as how technical expertise is advanced by regulatory agencies, have been scarce due to the limitations (1) in the conceptualization of diverse strategies to utilize scientific knowledge, and (2) the theorization of explanatory factors that account for variance in scientific risk assessments (Schrefler ; Rimkutė ).…”
Section: Introductionmentioning
confidence: 99%
“…The justification for such trust in experts rests on assumptions about their specialized knowledge and skills, which are commonly thought to produce more rational, well-founded decisions. Numerous studies have challenged these assumptions, however, with evidence suggesting that values also play a role in expert decision-making (Sabatier and Zafonte 2001;Barke and Jenkins-Smith 1993;Jenkins-Smith et al 2009;Rimkut_ e 2015;Haas 2004;Gottweis 1998). Despite this well-documented observation, calls for more deference toward experts continue, justified by the idea that policy decisions should be protected against the biases of activists, politicians and a relatively un-informed public (Weber and Stern 2011;Henderson 2012;Paarlberg 2008;Blinder 1997;Margolis 1996).…”
Section: Introductionmentioning
confidence: 99%